2023
DOI: 10.1002/biot.202300074
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and current advances in in vitro biofilm characterization

Ye Zhang,
Paul Young,
Daniela Traini
et al.

Abstract: Biofilms are structured communities of bacterial cells encased in a self‐produced polymeric matrix, which develop over time and exhibit temporal responses to stimuli from internal biological processes or external environmental changes. They can be detrimental, threatening public health and causing economic loss, while they also play beneficial roles in ecosystem health, biotechnology processes, and industrial settings. Biofilms express extreme heterogeneity in their physical properties and structural compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 162 publications
(233 reference statements)
0
2
0
Order By: Relevance
“…Although it has been reported that care must be taken in its clinical use, NO's ability to exogenously disrupt biofilms and destroy planktonic bacteria is finding its way into the literature with increasing frequency. 3,7,11,12,23,24 Recent developments in NO have proven it to be a novel approach to the treatment of antibiotic resistance and biofilm eradication. 3,4,[25][26][27][28][29] However, the usefulness of NO on biofilms is dose-dependent and is therefore based on the effectiveness of the delivery method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that care must be taken in its clinical use, NO's ability to exogenously disrupt biofilms and destroy planktonic bacteria is finding its way into the literature with increasing frequency. 3,7,11,12,23,24 Recent developments in NO have proven it to be a novel approach to the treatment of antibiotic resistance and biofilm eradication. 3,4,[25][26][27][28][29] However, the usefulness of NO on biofilms is dose-dependent and is therefore based on the effectiveness of the delivery method.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, effectual modes of action for eradication of biofilms must include a potentiated broad spectrum antimicrobial mechanism. [6][7][8] NO is an endogenous gasotransmitter that plays a vital role in wound healing. The reported and previously demonstrated bactericidal capability of NO gas supports myriad reasons for its clinical application.…”
Section: Introductionmentioning
confidence: 99%